Creativity and Innovation in the Age of Artificial Intelligence: A Copyright Dilemma - Ali, S. M. Aamir; Ghose, Anuttama; Saurav, Shashikant; Deshmukh, Sachin (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2024)
The advent of artificial intelligence marks a significant shift in creative domains traditionally dominated by human efforts, such as writing and painting. Artificial Intelligence challenges the intellectual property system with fundamental issues, including authorship and ownership. This paper explores the utilitarian dilemma related to the copyrightability of AI-generated content and re-evaluates the basis of natural rights, thereby questioning established copyright premises. It examines the manifestation of creativity in AI-based literary and artistic works, highlighting the current and changing aspects of copyright consideration. Additionally, the paper provides an exhaustive overview of the legal protections applicable to AI-generated works, specifically focusing on the legal context in India. It also explores the feasibility and suitability of establishing sui generis rights designed specifically to safeguard AI-generated content. The conclusions presented offer a detailed perspective on the complexities of aligning copyright laws with the dynamic nature of AI-enhanced creativity.